Hexacylloepus Hinton, 1940 rises again; 18 new species of a neglected genus (Coleoptera: Byrrhoidea: Elmidae) - Polizei, Thiago T.S. (2020)
The genus Hexacylloepus extends from the Neotropical region to the southwestern United States of America. At present, 25 species are known from 20 countries, with no new species proposed since 1972. In this paper, we describe and illustrate 18 new species (H. barrae; H. calori; H. casariae; H. froehlichi; H. geiseri; H. grandis; H. iassu; H. keitai; H. maierae; H. manauara; H. metapa; H. phalluspilosus; H. shorti; H. taylorae; H. thoracica; H. tibialis; H. ubirajarai; H. zaninii), from eight countries and give the first records of the genus from Suriname and Guyana.